Pengaruh Likuiditas Terhadap Struktur Modal dengan Profitabilitas sebagai Variabel Intervening - Ratu Wardatuddihan; Akhmadi Akhmadi; Enis Khaerunisa (Tirtayasa Ekonomika, 2021)
The purposed of this research to determine the effect of Liquidity proxy with Quick Ratio (QR) on Capital Structure which proxied by Debt to Assets Ratio (DAR) with Profitability proxied by Net Profit Margin (NPM) as intervening variable. The population in this study were all the Wholesale (Durable and Non Durable Goods) Sub sector companies which is listed on Indonesia Stock Exchange periode of 2013 - 2017. The sample in this study were 12 companies  out of 37 population obtained through purposive sampling method. Data analysis techniques used in this study were path analysis and sobel test. The results of this research are: (1) Liquidity (QR) negative and significant effect to Capital Structure (DAR), (2) Liquidity (QR) positive and significant effect to Profitability (NPM), (3) Profitability (NPM) negative and significant effect to Capital Structure (DAR), (4) Profitability (NPM) is not able to mediate the effect of Liquidity (QR) on Capital Structure (DAR).